Reflecting on what is “skill” in human motor skill learning - Yadav, Goldy; Duque, Julie (Frontiers in Human Neuroscience, 2023)
Humans have an exceptional ability to execute a variety of skilled movements. Researchers have been long interested in understanding behavioral and neurophysiological basis of human motor skill learning for advancing both fundamental neuroscientific knowledge and clinical outcomes. However, despite decades of work in this field there is a lack of consensus about what is meant by ‘skill’ in skill learning. With an advent of various task paradigms testing human motor behavior and increasing heterogeneity in motor learning assessments methods, it is very crucial to identify key features of skill in order to avoid any ambiguity that may result in misinterpretation or over-generalization of findings and have implications for replication work. In this review, we attempt to highlight the features of skill following a historical approach, considering the seminal work that led to the first definitions of skill and including also some contemporary concepts emerging from human motor learning research. Overall, based on this literature, we emphasize that skill has some fundamental characteristics, such as- i) optimal movement selection and execution, ii) improved movement speed and accuracy, and iii) reduced movement variability and error. These features of skill can emerge as a consequence of extensive practice/training/learning, thus resulting in a performance state beyond baseline level. We conclude that any neuroscientific endeavor aimed at understanding the essence of skill in human motor skill learning should focus on these aspects and provide some examples of tasks that can appropriately capture these features of skill.